Soy-derived phytochemical genistein modifies chromatome topology to restrict cancer cell proliferation - Dutta, Bamaprasad (2020)
Epidemiological data indicate that human cancer risk is significantly reduced by the consumption of soy-based foods containing the "phytoestrogen" genistein, which can signal via host cell estrogen receptors. While additional chemoprotective effects of genistein induced by epigenetic factors have also been reported, the key molecules and mechanisms involved are poorly defined. We therefore investigated genistein effects on chromatin-bound proteins in the estrogen receptor-deficient cell line MDA-MB-231 which is insensitive to phytoestrogen signaling. After exposure to low-dose genistein for >1 month, MDA-MB-231 cells exhibited stable epigenetic alterations that are analyzed via partial MNase digestion and TMT-based quantitative proteomics. 3177 chromatin-bound proteins are identified with high confidence, including 882 molecules that displayed altered binding topology after cell conditioning with genistein. Prolonged phytochemical exposure conferred heritable changes in the binding topology of key epigenetic regulators including ATRX, SUV39H1/H2, and HP1BP3 that are preserved in untreated progeny, resulting in sustained downregulation of proliferation genes and reduced cell growth. These data indicate that soy derivative genistein exerts complex estrogen receptor-independent effects on the epigenome likely to influence tumorigenesis by restricting cell growth.